К вопросу о механизме разупрочнения кристаллов синтетического алмаза при высокотемпературном нагревании - Майстренко, А.Л.; Боримский, А.И.; Девин, Л.Н.; Бологова, Л.М.; Щербаков, А.В.; Сулима, А.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
For the first time, with use of a method of acoustic emission, the effect of a cracking in synthetic diamonds at a stage of refrigeration after their heat is determined. It is fixed, that in the chips of diamond synthesised with application of alloys-solvents Fe95Si5 and Co88 (Cr3C2)12 cracking predominates in process heating up of chips, and in the chips synthesised with application of alloyssolvents Ni39,6Mn59,6Si0,8, Ni39,6Mn59,4(Cr3C2)1,0, Ni48Fe48(Cr3C2)4 and Fe26,4Co61,6(Cr3C2)12 – at refrigeration. With reduction of coefficient of thermal expansion of an alloy-solvent thermal stability of synthetic diamonds is refined.